Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1159/000050654
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Tumors of the Pancreas

Abstract: The discovery of a cystic lesion in the pancreas implies a challenge for the physician. Approximately 10% are cystic tumors, benign to highly malignant, or true cysts, showing all stages of cellular differentiation, from benign to highly malignant tumors. Malignant cystic tumors are rare and comprise only about 1% of all pancreatic malignancies, they are potentially curable. Therefore, correct diagnosis and treatment of these lesions are of great importance. It is usually not possible to separate a pseudocyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
(59 reference statements)
0
10
0
1
Order By: Relevance
“…Because of the potential risks of premaligancy or malignancy associated with pancreatic cysts, surgical resection has been advocated by some authors [3,5,6]. The justification for an aggressive approach is based on the inability to differentiate benign and malignant cysts, insufficient data on natural history, relatively high incidence of premalignant or malignant cysts, and low morbidity and mortality rate after pancreatic surgery [3,[5][6][7][8][9][10]. However, data collected after surgical resection do not reflect the characteristics of cystic neoplasms incidentally found in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the potential risks of premaligancy or malignancy associated with pancreatic cysts, surgical resection has been advocated by some authors [3,5,6]. The justification for an aggressive approach is based on the inability to differentiate benign and malignant cysts, insufficient data on natural history, relatively high incidence of premalignant or malignant cysts, and low morbidity and mortality rate after pancreatic surgery [3,[5][6][7][8][9][10]. However, data collected after surgical resection do not reflect the characteristics of cystic neoplasms incidentally found in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that PDAC may be accompanied by cystic changes within or adjacent to the mass, and that the incidence of PDAC with cystic changes ranges from ,1% to 8% [3,4]. Radiologists should be familiar with PDACs with cystic changes as they may resemble more common cystic pancreatic lesions, such as pseudocysts, intraductal papillary mucinous neoplasms (IPMNs), solid pseudopapillary tumours and non-functioning islet cell tumours, all of which are managed differently and usually have better patient survival rates [5][6][7].Many studies have discussed the radiological appearance of PDAC accompanied by cystic lesions [6][7][8][9][10][11].Most of these studies have discussed pseudocysts or retention cysts depicted adjacent to the PDAC or in the extrapancreatic area in the clinical setting of pancreatitis [8][9][10][11], whereas only a few studies have discussed intratumoral cystic lesions, such as cystic necroses, in larger ordinary PDACs [6,7]. Some case reports have described the intratumoral cystic changes of PDAC variants, i.e.…”
mentioning
confidence: 99%
“…However, recent studies have shown that PDAC may be accompanied by cystic changes within or adjacent to the mass, and that the incidence of PDAC with cystic changes ranges from ,1% to 8% [3,4]. Radiologists should be familiar with PDACs with cystic changes as they may resemble more common cystic pancreatic lesions, such as pseudocysts, intraductal papillary mucinous neoplasms (IPMNs), solid pseudopapillary tumours and non-functioning islet cell tumours, all of which are managed differently and usually have better patient survival rates [5][6][7].…”
mentioning
confidence: 99%
“…Therefore, most incidental pancreatic cystic lesions are assumed to be cystic neoplasms. Because of the as-yet-undefined but nevertheless present risk of malignancy, the aggressive approach of surgical resection of these pancreatic cysts has been advocated by some authors [2,4,5]. This recommendation is in contradistinction to the prevailing practice at our institution for small cystic lesions of 2 cm or smaller.…”
mentioning
confidence: 99%